Salivary metabolic signatures of carotid atherosclerosis in patients with type 2 diabetes hospitalized for treatment - Sakanaka, Akito; Katakami, Naoto; Furuno, Masahiro; Nishizawa, Hitoshi; Omori, Kazuo; Taya, Naohiro; Ishikawa, Asuka; Mayumi, Shota; Inoue, Moe; Tanaka Isomura, Emiko; Amano, Atsuo; Shimomura, Iichiro; et al. (Frontiers in Molecular Biosciences, 2022)
Atherosclerosis is a life-threatening disease associated with morbidity and mortality in patients with type 2 diabetes (T2D). This study aimed to characterize a salivary signature of atherosclerosis based on evaluation of carotid intima-media thickness (IMT) to develop a noninvasive predictive tool for diagnosis and disease follow-up. Metabolites in saliva and plasma samples collected at admission and after treatment from T2D patients hospitalized for two weeks to undergo medical treatment for diabetes were comprehensively profiled using metabolomic profiling with gas chromatography-mass spectrometry. Orthogonal partial least squares analysis, used to explore the relationships of IMT with clinical markers and plasma and salivary metabolites, showed that the top predictors for IMT included salivary allantoin and 1,5-anhydroglucitol (1,5-AG) at both the baseline examination at admission and after treatment. Furthermore, though treatment induced alterations in salivary levels of allantoin and 1,5-AG, it did not modify the association between IMT and these metabolites (pinteraction >0.05), and models with these metabolites combined yielded satisfactory diagnostic accuracy for the high IMT group even after treatment (area under curve = 0.819). Collectively, this salivary metabolite combination may be useful for noninvasive identification of T2D patients with a higher atherosclerotic burden in clinical settings.